Keanekaragaman Hayati Ekosistem Mangrove Lantebung - Wulandari, Sri; Suprianto, Suprianto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2023)
Mangrove ecosystems provide high biodiversity because, in addition to being inhabited by various types of vegetation, another role is to provide important areas used by various fauna species for spawning, nurturing, and feeding. This scientific article is a literature review. The data obtained is then analyzed and presented descriptively. The sources of data are reliable scientific references and various relevant sources of information including direct visual observations. The results of the study show that mangrove vegetation found in the Lantebung Mangrove Ecosystem is six species namely Rhizopora mucronata, Rhizopora apiculata, Bruguiera gymnorhiza, Avicennia marina, Avicennia alba, and Sonneratia alba. The mangrove fauna consists of classes of aves, Pisces, reptiles, crustaceans, Insecta as well as several species of gastropods, other macrozoobenthos, and phytoplankton. The Lantebung Mangrove Ecosystem has the potential to provide more biodiversity if mangrove management is carried out comprehensively.